A bibliometric analysis of customer experience in the omni-channel era - (:unkn) unknown (Taylor & Francis, 2024)
In the fiercely competitive market, coordinating physical and digital channels to deliver a seamless omnichannel customer experience (OCX) has become crucial after the COVID-19 pandemic. However, existing research on OCX lacks a comprehensive understandi...
Keywords: Experiencia del cliente; Omnicanalidad